Coronary bifurcation lesions: is less more? - Bennett, Johan; Dubois, Christophe (Journal of Thoracic Disease, 2016)
Coronary bifurcation lesions are frequent in everyday practise and account for up to 20% of all percutaneous coronary interventions (PCI) (1). The treatment of bifurcation lesions with drug-eluting stents (DES), especially when a double stent technique is used, remains challenging and is associated with a lower procedural success rate and a higher rate of long-term adverse cardiac events such as stent restenosis and thrombosis compared to non-bifurcation PCI (2). The question relating to a one or two stent strategy for bifurcation lesions has been a subject of many debates over recent years and numerous observational and randomized studies (3-6) have supplied data to this important though at times controversial subject.